(untitled) (World Bulletin of Public Health, 2024)
Hernia is a common surgical case that requires intervention to prevent complications and ensure quality of life for the patient. In this article, we present a comparative analysis of different methods of surgical treatment for hernia, evaluating their efficacy based on statistical data. Hernia, although not a life-threatening condition, can significantly affect the patient’s quality of life, causing pain and limiting physical activity. Surgical treatment of hernias is an effective method of eliminating this condition, and the choice of hernia repair method may be important to successful outcomes